A Conceptual Framework for Creating Transition Plans for Incarcerated Youth (Journal of Applied Juvenile Justice Services, 2020)
Incarcerated youth face many challenges as they transition back to the community. The development and implementation of person-centered transition plans have been shown to improve re-engagement in education and employment, and to reduce recidivism. There is, however, little research to guide personnel in juvenile justice settings as to what a transition plan should contain and how it could be implemented. This article offers a conceptual framework based on transition theories, the extant research literature on transition plans and services, and practitioner experience to inform transition plan components for all young people in custody, with a focus on youth with disabilities and in out-of-home care.